Hercule, le lion et le cheval : les bronzes romains du puits 269 de Châteaumeillant/Mediolanum (Cher) - Sophie Krausz; Gérard Coulon (Gallia, 2015)
The excavation of the Gallic oppidum of Châteaumeillant-Mediolanum in 2012, yielded a remarkable deposit in the bottom of a Gallo-Roman well. It included nearly 6 000 diverse fragments, including ceramics, animal bones, defixionum tabellae and the remains of a four-wheel cart. Amongst these, four exceptional bronze objects were discovered an oinochoe (wine jug) with a trefoil spout, the front part of a chest, a horse’s head featuring a long pouring spout and a solid bronze lion with silver-incrusted eyes. Although their archaeological studies aren’t completed yet, this paper presents a preliminary examination of these four bronze objects and our first hypotheses about them.